Aggregate Hours Adjustment in Frictional Labor Markets - Michael Krause; Thomas A. Lubik (Verein für Socialpolitik, 2010)
We evaluate the ability of the labor market search and matching framework to account for the variation in aggregate hours worked. The model we develop and estimate features search frictions in the labor market, capital and investment adjustment costs, as well as variable hours at the worker level. Firms and workers bargain efficiently over wages and hours worked, and relative price setting is monopolistic. Driving forces of aggregate fluctuations are assumed to be productivity, preference, markup, and investment-speci c shocks. We estimate the model on aggregate and labor market data for the U.S. using Bayesian techniques. We find that product market (markup) shocks are important to explain aggregate employment dynamics. We explore various mechanisms that help match the hours worked/employment correlation.
Keywords: J63; E24; J23; 330; Bayesian Estimation; Unemployment; Vacancies; Investment-specific Shocks